The Evolving Landscape of Hepatocellular Carcinoma: A US Safety Net Collaborative Analysis of Etiology of Cirrhosis - Lee, Rachel M. (Am Surg, 2020)
BACKGROUND: Hepatitis C virus (HCV) has historically been the most common cause of cirrhosis and hepatocellular carcinoma (HCC) in the United States. With improved HCV treatment, cirrhosis secondary to other etiologies is increasing. Given this changing epidemiology, our aim was to determine the impact of cirrhosis etiology on overall survival (OS) in patients with HCC. METHODS: All patients with cirrhosis and primary HCC from the US Safety Net Collaborative (2012-2014) database were included. Patients were grouped into “safety net” and “academic” based on where they received their care. The primary outcome was the OS. RESULTS: 1479 patients were included. The average age was 60 years and 78% (n = 1156) were male. 56% (n = 649) received care at academic and 44% (n = 649) at safety net hospitals. The median model for end-stage liver disease (MELD) was 10 (IQR 8-16). Median OS was 23 months. Etiology of cirrhosis was viral hepatitis 56% (n = 612), alcohol abuse 14% (η = 152), alcohol and hepatitis 23% (n = 251), and other 7% (n = 85). Patients with alcohol-related cirrhosis (alcohol alone or with hepatitis) were younger (59 vs 62 years), more likely to be male (86% vs 75%), treated at a safety net facility (45% vs 35%), uninsured (17% vs 13%), and had a higher MELD (median 12 vs 10) (all P < .003). They were less likely to have been screened for HCC within 1 year of diagnosis (20% vs 29%) and to receive treatment (69% vs 81%), and more likely to present with stage IV disease (21% vs 15%) (all P < .001). Patients with alcohol-related cirrhosis had decreased OS (5-year OS 24% vs 40%, P < .001), which persisted in a subset analysis of both academic and safety net populations. CONCLUSION: Although not significant on MVA, alcohol-related cirrhosis is associated with all factors that correlate with decreased survival from HCC. Efforts must focus on this vulnerable patient population to optimize screening, treatment, and outcomes.